PEMBERIAN PUPUK ORGANIK CAIR ECENG GONDOK TERHADAP HASIL CABAI RAWIT (Capsicum frutescent L.) - Linda Rahmawati; Riska Riska; Mila Lukmana; Muhammad Helmy Abdillah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
ABSTRACTLiquid organic fertilizer (LOF) is proven to be more effective than solid organic fertilizer because nutrient mineralization is more efficient, so nutrients are quickly available for plants. Water hyacinth, as a water weed, turns out to have many functions. Besides being able to become a biofilter by absorbing chemical compounds in polluted water, the accumulation results also contain mineral compounds that are useful for increasing plant yields. Therefore, it is necessary to review the results of applying LOF made from water hyacinth to cayenne pepper plants. This study aims to analyze the effect of various doses of water hyacinth extract on the yield of cayenne pepper. This study uses a non-factorial experimental method, a complete random design (CRD), with an analysis model of LSD test (Least Significant Difference Test) α 5%. There are 4 treatments, namely, 0 ml, 40 ml, 60 ml, and 80 ml, with 5 replications. The parameters observed are the number of fruits, the fruit weight, and the wet weight of the plant. The results showed that the water hyacinth LOF has a pH of 7, doesn’t sting, and is light brown. The best treatment for P3 or 80 ml of water hyacinth POC is that the average number of fruits is 10 seeds, the average weight of fruit is 2.04 grams, and the average wet weight of plants is 46.9 grams.